FLIGHT PATH CONTROL FOR UNMANNED AERIAL VEHICLE - M. A. Al-Mashhadani (Системный анализ и прикладная информатика)
Studying the optimized control law specified criteria on UAV while hovering over a path defined by the reference points in the inertial frame. An illustrative example is the  theoretical efficiency of the proposed provisions.